Spiritual Perception and Attitude Toward Spiritual Care Competence Among Nursing Students - A. Adriana Amal; Syamsiah Rauf; Saldi Yusuf (GLOBAL HEALTH SCIENCE GROUP, 2022)
Spiritual care competence is one of the important competencies that must be developed in nursing students in the educational process. Perception, attitude and spiritual competence are the main factors which will help nurses in providing patient's spiritual needs. This study aimed to see the relationship between spiritual perception and attitude toward spiritual competence in nursing students. Using quantitative descriptive with a cross sectional approach, the data was collected from 222 respondents obtained by purposive sampling technique. The Spiritual Care Competency Scale (SCCS) questionnaire was used to assess spiritual care competence, the Spiritual Attitude and Involvement List (SAIL) to assess spiritual attitude, and the Spirituality and Spiritual Care Rating Scale (SSCRS) to assess spiritual perception. Data were analyzed using the Spearman test. The findings revealed a positive relationship between spiritual perception and attitude, and spiritual care competence with a significance value of <0.0001. Spearman's correlation values ​​were respectively 0.692 with a strong correlation strength and 0.565 with a moderate correlation strength. In conclusion, there is a correlation in a positive direction between spiritual perception and attitude, and the competence of spiritual care in nursing students.